PENERAPAN METODE SIMPLEKS UNTUK MINIMASI BIAYA PRODUKSI PADA PENJUALAN DONAT MISEL - Rina Hawase; Heru sutejo, Djonathan Tuange, Medi Tabuni, Deby Womsiwor, Sumina Yawan, Shasa Rumsarwir (CV. Adiba Aisha Amira, 2026)
Donat Misel is a micro, small, and medium enterprise (UMKM) engaged in donut production and sales that faces challenges in controlling production costs due to limited resources and fluctuating raw material prices. This study aims to determine the minimum production cost using the Simplex Linear Programming method. Research data were collected through observation, interviews, and literature studies, including information on raw material usage, production costs, production capacity, and working time. A linear programming model was formulated consisting of an objective function to minimize production costs and several constraint functions related to working time, raw materials, and revenue limitations. The calculation process was carried out using QM for Windows V5 software. The results showed that the optimal solution was obtained at variable X1 (Sugar Donut) with a production quantity of 50 units, while variables X2 (Chocolate Sprinkle Donut) and X3 (Cheese Donut) had values of zero. These findings indicate that the Simplex method can generate an optimal production combination, minimize production costs, and improve resource utilization efficiency in Donat Misel MSME.